2022
DOI: 10.3390/jmse10070950
|View full text |Cite
|
Sign up to set email alerts
|

AUV Formation Coordination Control Based on Transformed Topology under Time-Varying Delay and Communication Interruption

Abstract: Aiming at the control problem of autonomous underwater vehicle (AUV) pilot-following formation with communication delay and communication interruption, a controller based on feedback linearization and the PD control method is designed in this paper. Firstly, the nonlinear, strongly coupled vehicle model is transformed into a second-order model via the feedback linearization method, and then the formation coordination controller is designed based on consistency theory and the PD control method. The Markov rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Based on the Lee derivative [24] and the definition of g(x), for any 1 ≤ i ≤ 10, 1 ≤ j ≤ 10, it follows that…”
Section: Of 17mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the Lee derivative [24] and the definition of g(x), for any 1 ≤ i ≤ 10, 1 ≤ j ≤ 10, it follows that…”
Section: Of 17mentioning
confidence: 99%
“…d(i) is the number of AUVs that can transmit information to any single U in the formation AUV. If the AUV formation members can communicate in both directions, based on the principle of the graph theory, it is indicated that graph A is an undirected graph, as shown in Figure 2 [24].…”
Section: Formation Communication Topologymentioning
confidence: 99%
“…Theorem 1. Under the Assumption 1 that the UUV group communication topological graph is an undirected connected graph and satisfies Assumption 2, then under the consistency control protocol (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), if the speed control gain satisfies the following inequality:…”
Section: Consensus Control For Distance To the Targetmentioning
confidence: 99%
“…Formation coordination ability [6,7] is necessary for UUV groups to perform tasks. Although the research on formation coordination control of UUVs started late, it has great potential in practical applications [8][9][10].…”
Section: Introductionmentioning
confidence: 99%